Identifikasi Kualifikasi Tenaga Pengelola Gedung Terstandar Dalam Peningkatan Nilai Gedung Tinggi di Jawa Timur - Lexi Pranata Budidharmanto Limbing (Universitas 17 Agustus 1945 Surabaya, 2015)
The growth of high-rise buildings in East Java is increasing rapidly. High-rise building which has stood for a long time have to compete with the new high-rise building in improving occupancy and resale value of the asset. Maintenance and facility management are important key factors in improving occupancy and the sale value of the asset. The diversity of the success rate of high-rise building in the competition is determined by the ability of the property manager or general manager in planning and effective implementation of his or her maintenance programs, and financial, technical, resources management, and leadership to the team. The sharpness intuition which property manager or general manager have in seeing opportunities and market direction of high-rise buildings become a supporting but important factor, where the mindset of entrepreneurship is taking the part in.This is justified by the recognition of practitioners and experts are now actively working in the field of building management in the interview (descriptive) and recorded in a questionnaire that can be measured by a percentage (quantitative), as result entirely agree that standardization competence, educational background and the lack of entrepreneurship mindset the only cause and needs to be invested to improve the competitiveness of a building practitioners, especially now we are facing the Asean Economic Community (AEC).Â Key words: entrepreneurship, standardization, competency, building, highrise